Groups of Periodically Defined Linear Transformations of an Infinite-Dimensional Vector Space - Bezushchak, O. E.; Sushchanskii, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
The notions of periodically defined and residual periodically defined linear transformations of an infinitedimensional vector space V over the field K are introduced. A group of all strictly residual periodically defined transformations and its subgroups of u-periodically defined transformations (where u is a supernatural number) are investigated. A continual family of simple groups obtained as infinite-dimensional analogs of PSL_n (K) is constructed.